Persistent Disparities Among Patients With T-Cell Non-Hodgkin Lymphomas and B-Cell Diffuse Large Cell Lymphomas Over 40 Years: A SEER Database Review - Crozier, Jennifer A.; Sher, Taimur; Yang, Dongyun; Swaika, Abhisek; Foran, James; Ghosh, Radhika; Tun, Han; Colon-Otero, Gerardo; Kelly, Kevin; Chanan-Khan, Asher; Ailawadhi, Sikander (Clinical lymphoma, myeloma and leukemia, 2015)
Our population-based analysis for T-cell and B-cell non-Hodgkin lymphoma (NHL) in the novel therapeutic agent era showed worse median overall survival (OS) for male subjects, older patients, and ethnic minorities for both T-cell and B-cell NHL. Despite novel therapeutics targeting T cells, there has been no statistically significant improvement in OS over time, in contrast to the significant improvement in B-cell NHL OS, presumably as a result of the advent of monoclonal antibodies. As of 2013, more than 550,000 people are living with non-Hodgkin lymphoma (NHL). We undertook a large Surveillance Epidemiology and End Results (SEER) based analysis to describe outcome disparities in different subgroups of aggressive T-cell and B-cell NHL patients, with a focus on various ethnicities. The final analysis included 7662 patients with T-cell and 84,910 with B-cell NHL. Survival analysis revealed that male sex and increasing age were independent predictors of worse overall survival (OS; P < .001). For aggressive T-cell NHL, there was no significant improvement in median OS between 1973 and 2011 (P = .081), and ethnic minorities (Asians, Hispanics, and African Americans) had significantly worse OS than whites (P < .001). There were similar trends for age, sex, and race for diffuse large B-cell NHL, but a significant improvement in median OS was seen over time (P < .001). These results are the first to elicit outcomes in a broad classification of ethnic minorities and underscore the urgency for development of novel therapeutics, especially in T-cell NHL. In addition, in-depth studies of disease biology and health care utilization are required for better triage of health care resources, especially for ethnic minorities.